Analisis Rasio Keuangan Pada Perusahaan Sub Sektor Logam & Sejenisnya Serta Sub Sektor Kimia Yang Terdaftar di BEI Periode 2017-2018 - Sonivia Gunawan; Leviandi Adhie (Winter Journal: IMWI Student Research Journal, 2022)
This analysis was conducted to see the performance of companies in the metal & allied product sub sector and chemical sub sector listed on the Indonesia Stock Exchange (IDX) using financial ratio analysis. The research method used in this research is descriptive research method. The data used is secondary data, in the form of financial statements for the period 2017-2018, which are published on the IDX website. The data used is the financial statements of 29 companies. Financial ratio analysis used is the current ratio, operating profit margin, return on assets, return on equity, earning power of total investment, debt to assets, debt to equity, total assets turnover, and fixed assets turnover. The result of analysis shows an increase and a decrease.